Exploring minocycline's effect on retinal degeneration following N-methyl-N-nitrosourea exposure in rats - B Karabulut; H Eroksuz; Y Eroksuz; M Gul (Veterinární Medicína)
Retinal degeneration (RD) is often associated with deficiencies or the inaccurate production of photoreceptor-specific proteins, which are encoded by various genes and characterised by the apoptotic and ongoing death of photoreceptor cells. This study involved administering a single intraperitoneal (i.p.) dose of 50 mg/kg of N-methyl-N-nitrosourea (MNU) to rats to induce RD. Some of these rats also received intraperitoneal minocycline at varying doses to prevent RD. Euthanasia was conducted at five intervals: at 12, 24, 48, and 72 h, and on the 7th day; and eye samples were taken. These samples were analysed using histopathology, immunohistochemistry, and electron microscopy. Significant RD was observed in the MNU-treated groups, with photoreceptor cell apoptosis demonstrated by the TUNEL method. Compared with those in the control group, there was a progressive thinning of the photoreceptor layer and outer nuclear layer, along with increased levels of glial fibrillary acidic protein (GFAP) and proliferating cell nuclear antigen (PCNA), and reduced levels of rhodopsin and red/green opsin starting from the 12th hour in the experimental groups. Electron microscopy revealed that amacrine and bipolar cells, in addition to photoreceptors, were also affected. The minocycline treatment did not show significant differences in retinal layer thickness or the staining levels of PCNA, GFAP, and opsins in the MNU-induced RD model.